Sustainability in the pharmaceutical industry—An assessment of sustainability maturity and effects of sustainability measure implementation on supply chain security - Celina Bade; Alexandra Olsacher; Philip Boehme; Hubert Truebel; Lena Bürger; Leonard Fehring (Corporate Social Responsibility and Environmental Management, 2023)
The pharmaceutical industry faces increased sustainability demands. The Environmental, Social, and Governance (ESG) framework is most widely accepted to discuss corporate sustainability, but little is known about the effects of ESG measure implementation on supply chain security. Understanding these effects is especially important in the face of drug shortages. Leveraging a quantitative and a qualitative method based on a grounded theory approach, we aim to investigate the state of ESG maturity of pharmaceutical corporations in Germany and develop a perspective on the effects of ESG measure implementation on supply chain security. We find publicly traded~and larger companies having higher ESG target-setting maturity than privately-owned or smaller companies and that company priorities, costs, and regulatory processes limt ESG progress overall. Our findings suggest that ESG measure implementation can induce short-term supply disruption risks. A risk assessment considers current ESG maturity, implementation effects outside of own operations, short-term supply buffers, implementation timeline, and scope, and change management capabilities.
Keywords: 650; corporate sustainability; drug shortage; ESG; supply chain security; supply disruption; sustainability